(untitled) (Research, Society and Development, 2020)
The objective was to evaluate the microbiological quality of water and milk from agroecological and conventional properties in western Paraná. The collections were carried out in 20 conventional properties in the municipality of Santa Helena - PR, and in 27 agroecological bases and in Diamante d’Oeste and Ramilândia - PR. Milk collections were carried out in different production systems and seasons. Were analyzed the contamination of thermotolerant coliforms (ThermC), total coliforms (TC), enterobacteria, aerobic mesophiles (AM), determination of chemical composition, somatic cell count (SCC) and total bacterial count (TBC). There was no difference in milk composition between summer production systems. In relation to SCC during the winter, 44.4% and 55.0% of the properties presented values ​​above 600 thousand cells mL-1, in the agroecological and conventional systems, respectively. In both seasons, most of the agroecological properties are above 600 thousand CFU mL-1 of TBC. In both production systems and seasons, the AM values ​​were lower than those allowed by NI76, and there was no difference for enterobacteria in milk. The count of milk TC in winter was similar between the two production systems. For the water samples for cleaning the milking equipment, the TC and ThermC values were higher in the agroecological system. The use of management practices is recommended in order to reduce the SCC and TBC values ​​of milk produced in the western of Paraná to conform to the values required by NI76.